2021
DOI: 10.3390/agronomy11071409
|View full text |Cite
|
Sign up to set email alerts
|

Technologies for Forecasting Tree Fruit Load and Harvest Timing—From Ground, Sky and Time

Abstract: The management and marketing of fruit requires data on expected numbers, size, quality and timing. Current practice estimates orchard fruit load based on the qualitative assessment of fruit number per tree and historical orchard yield, or manually counting a subsample of trees. This review considers technological aids assisting these estimates, in terms of: (i) improving sampling strategies by the number of units to be counted and their selection; (ii) machine vision for the direct measurement of fruit number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 106 publications
(162 reference statements)
1
35
0
Order By: Relevance
“…Tomato plant dry matter production was found to be superior at cornstarch SAP 1-kg rates compared with all other rates. Although this did not translate directly into higher yields at this rate, there is a high correlation between higher biomass and greater plant yields in most horticultural crops (Anderson et al, 2021;Marcelis et al, 1998). Similar results were observed by Zangooei-Nasab et al (2012), who found that plant height, dry weight of aerial organs, and root dry weight of Saxaul seedlings was improved by 0.1%, 0.2%, 0.3%, and 0.4% rates of Stockosorb.…”
Section: Discussionsupporting
confidence: 78%
“…Tomato plant dry matter production was found to be superior at cornstarch SAP 1-kg rates compared with all other rates. Although this did not translate directly into higher yields at this rate, there is a high correlation between higher biomass and greater plant yields in most horticultural crops (Anderson et al, 2021;Marcelis et al, 1998). Similar results were observed by Zangooei-Nasab et al (2012), who found that plant height, dry weight of aerial organs, and root dry weight of Saxaul seedlings was improved by 0.1%, 0.2%, 0.3%, and 0.4% rates of Stockosorb.…”
Section: Discussionsupporting
confidence: 78%
“…With the introduction of computer vision in the smart agriculture domain, fruit detection and tracking technologies, which can help to obtain fruit yield statistics and assist with automatic fruit picking and automated orchard management, have become important areas of research. Anderson et al [ 1 ] pointed out that yield prediction can help growers with farming decisions for the season, especially in regard to labor allocation for harvesting, fruit transportation, and storage methods. An experienced agronomist can use these resources and combine this information with knowledge of fruit tree physiology to provide advice on the current season and make recommendations on management practices for optimizing orchard development.…”
Section: Introductionmentioning
confidence: 99%
“…An experienced agronomist can use these resources and combine this information with knowledge of fruit tree physiology to provide advice on the current season and make recommendations on management practices for optimizing orchard development. Anderson et al [ 1 ] also pointed out that fruit yield prediction can now be broadly classified into five methods. Fruit yield estimation is a labor-intensive, monotonous, and tedious task.…”
Section: Introductionmentioning
confidence: 99%
“…High-performance visual perception systems (as a key technology for automated fruit operation system in orchards) can be applied to smart orchard such as fruit positioning [1,2], orchard yield statistics [3,4], and automatic fruit picking [5,6], by combining intelligent mechanical equipment. However, most current visual detection techniques are based on strongly supervised models of deep learning [7][8][9][10][11] that rely on labeled datasets to support the model training.…”
Section: Introductionmentioning
confidence: 99%